2016
DOI: 10.1016/j.biocel.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Absence of AMPKα2 accelerates cellular senescence via p16 induction in mouse embryonic fibroblasts

Abstract: Emerging evidence suggests that activation of adenosine monophosphate-activated protein kinase (AMPK), an energy gauge and redox sensor, delays aging process. However, the molecular mechanisms by which AMPKα isoform regulates cellular senescence remain largely unknown. The aim of this study was to determine if AMPKα deletion contributes to the accelerated cell senescence by inducing p16INK4A (p16) expression thereby arresting cell cycle. The markers of cellular senescence, cell cycle proteins, and reactive oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…It has been labeled as an anti-aging and anti-inflammatory molecule [5, 6]. Our preliminary findings show the reduction of AMPKα1 phosporylation at Thr-172 in lungs of COPD pateints as compared to nonsmokers (data not shown).…”
Section: Discussionmentioning
confidence: 60%
“…It has been labeled as an anti-aging and anti-inflammatory molecule [5, 6]. Our preliminary findings show the reduction of AMPKα1 phosporylation at Thr-172 in lungs of COPD pateints as compared to nonsmokers (data not shown).…”
Section: Discussionmentioning
confidence: 60%
“…Sections were successively incubated in endogenous peroxidase and alkaline phosphatase block buffer (Dako, Glostrup, Denmark), protein block buffer and primary antibodies, which were incubated with the sections overnight at 4°C. After rinsing in wash buffer, sections were incubated with labelled polymer–horseradish peroxidase anti‐mouse or anti‐rabbit antibodies and 3,3'‐diaminobenzidine (DAB) chromogen as described previously (Ding et al , ). After a final wash, the sections were counterstained with haematoxylin.…”
Section: Methodsmentioning
confidence: 99%
“…Oncogene H-RasV12-transformed WT MEFs dramatically develops tumors in nude mice [ 5 ], which is contrast to the results reported by Phoenix et al [ 8 ]. H-RasV12-transformed AMPKα1α2 double KO MEFs fails to form tumors in mice [ 5 ], which may be due to the increased cellular senescence in AMPKα2-KO MEFs [ 38 ]. Here, we showed that AMPKα1 deletion stimulated anchorage-independent MEF growth, which is consistent with a previous report that AMPKα1 deletion triggers MEF hyperproliferation and DNA damage [ 39 ].…”
Section: Discussionmentioning
confidence: 99%